Epistemological anarchism of Paul Karl Feyerabend and medical education - Gomes, Andréia Patrícia; Siqueira-Batista, Rodrigo; Rego, Sergio (Revista Brasileira de Educação Médica, 2013)
The thoughts of the philosopher Paul Karl Feyerabend brought important contributions to the debate on Science in the 20th century. Most recently his views about non-existence of a single method for doing science have been employed to rethink science education and propose the use of multiple methods for effective teaching-learning process. This article employs the theoretical framework of the author expressed in the book Against Method, 1977, about the epistemological anarchism and the methodological pluralism and uses it in the contemporary discussion of medical education.

O pensamento do filósofo Paul Karl Feyerabend trouxe importantes contribuições ao debate sobre a ciência no século XX. Mais recentemente suas ponderações acerca da não existência de um único método para se fazer ciência têm sido empregadas para repensar a educação científica e propor a utilização de múltiplos métodos para o efetivo processo de ensino-aprendizagem. O objetivo deste artigo é empregar os referenciais teóricos do autor expressos no livro Contra o Método, de 1977, acerca do anarquismo epistemológico e do pluralismo metodológico, e utilizá-los na discussão contemporânea da educação médica.
Keywords: Knowledge; Methods; Medical Education; Human Resources Formation